1987
DOI: 10.1007/bf03180009
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and reproduction in haematophagous arthropods

Abstract: Hosts of haematophagous arthropods range from amphibians to mammals. Blood meal is essential for egg production. Quantity and quality of ingested blood are important in realization of optimum reproductive potentials. In terms of egg production, the lowest nutritive value is for human blood. This inequality is probably based on differences in proteins and their constituent amino acids. Carbohydrates in the diet have no direct contribution to reproduction. Very little is known about sterol. lipid, vitamin and sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 124 publications
0
7
0
Order By: Relevance
“…In addition, although artificial membrane feeding systems exist, in which mosquitoes are required to land on and bite through a membrane surface of a container of human blood, wild-caught vectors typically require a period of “training” before readily accepting blood under these conditions. The primary reasons for using humans rather than an alternative animal blood source include: (1) anthropophagy (some mosquitoes will only feed on human blood); and (2) differences between human and animal blood (proteins and their constituent amino acids) that could affect vector fitness ( i.e ., survival) and therefore behavior (Prasad 1987 ).…”
Section: The Role Of Humans In Vbrmentioning
confidence: 99%
“…In addition, although artificial membrane feeding systems exist, in which mosquitoes are required to land on and bite through a membrane surface of a container of human blood, wild-caught vectors typically require a period of “training” before readily accepting blood under these conditions. The primary reasons for using humans rather than an alternative animal blood source include: (1) anthropophagy (some mosquitoes will only feed on human blood); and (2) differences between human and animal blood (proteins and their constituent amino acids) that could affect vector fitness ( i.e ., survival) and therefore behavior (Prasad 1987 ).…”
Section: The Role Of Humans In Vbrmentioning
confidence: 99%
“…The studies conducted also provide a glimpse into the genetic compliment involved with blood feeding, which includes secreted salivary proteins, catalytic and transport processes associated with digestion and egg production (vitellogenesis). As was found in the transcriptome analyses of the malaria vector Anopheles gambiae ( Dana et al, 2005 , Marinotti et al, 2006 ), characteristic genes were identified that are associated with hematophagy, including serine proteases, trypsins, cytochrome oxidases, anti-coagulation factors and vitellogenins which have recently been reported to play a major functional role in acquisition, processing and utilization of the blood meal and its components ( Gulia et al, 2010 , Kokoza et al, 2001 , Prasad, 1987 , Ramalho-Ortigao et al, 2003 ). The identification and expression profiles of genes associated with hematophagy as well as defense can be critical in understanding the biological functioning of Culicoides and may well provide a platform for the development of molecular targets for altering vector competence or controlling vector populations.…”
Section: Culicoides Sonorensis Transcriptome and Genome Projmentioning
confidence: 84%
“…Differences occurring between ,¥21 and ,¥22 may be attributed to the geometry of the imidazole ring, which lacks twofold symmetry, to the smaller size of the imidazole ring as compared to phenyl, and to the hydrogen-bonding interactions of the nitrogen atoms (Benedetti, Morelli, Nemethy & Scheraga, 1983). Intermolecular hydrogen bonding (Table 5) (Kim & Rich, 1967) but is rather short when compared to other N--H...N interactions (2.90-3.0 A) (Voet & Rich, 1970;Prasad & Govil, 1980 An extensive network of hydrogen-bonding interactions also exists between the five water molecules which occupy channels in the xy plane of the crystal lattice as indicated in Fig. 2.…”
Section: Comparison Of Torsion Angles (O)for Various Histidines X J =mentioning
confidence: 99%